Carbon Emission Disclosure and Firm Value: Does Eco-Efficiency Moderate this Relationship? - Ajeng Rahmianingsih; Melinda Malau (International Journal of Social Service and Research, 2022)
The purpose of this research is to analyze the effect of Carbon Emission Disclosure and Firm Value on moderate of Eco efficiency relationship. Carbon Emission Disclosure as an independent variable is measured by dummy. Firm value as dependent variable is measured by Tobins’Q. This research using Leverage, Firm Size, profitability as control variable. The research uses 495 samples, comprising the data of 99 manufacturing companies listed on the Indonesia Stock Exchange over five years, from 2017 to 2021. The sampling method in this research is purposive sampling. The analysis technique in this study using multiple linear regression analysis. The results show that Carbon Emission Disclosure has a significant positive influence on the Firm Value, while Eco-Efficiency has a significant negative influence. The implications of this research it is hoped that investors will be increasingly concerned about the environment by considering the environmental impacts produced by companies as a consideration for determining investment decisions because investors are one of the parties that can pressure companies to implement environmental policies.